2016
DOI: 10.1016/j.jhep.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Laminin-332 sustains chemoresistance and quiescence as part of the human hepatic cancer stem cell niche

Abstract: In this study we identified a prominent role for laminin-332 as part of the specialised CSC niche in maintaining and supporting cell 'stemness', which leads to chemoresistance and quiescence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 117 publications
(109 citation statements)
references
References 34 publications
8
100
1
Order By: Relevance
“…In this milieu, Ln‐332 is distributed along the advancing edge of the tumor, correlated with a worse prognosis . In addition, Ln‐332 is expressed in the cancer stem cell niche, promoting the expression and maintenance of the stemness phenotype . This is also consistent with a recent study demonstrating that Ln‐332 and TGF‐β are correlated with overall survival in intrahepatic cholangiocarcinoma, while in HCC Ln‐332 cooperates with TGF‐β1, triggering the epithelial‐mesenchymal transition and promoting a more invasive and aggressive phenotype .…”
Section: Discussionsupporting
confidence: 89%
“…In this milieu, Ln‐332 is distributed along the advancing edge of the tumor, correlated with a worse prognosis . In addition, Ln‐332 is expressed in the cancer stem cell niche, promoting the expression and maintenance of the stemness phenotype . This is also consistent with a recent study demonstrating that Ln‐332 and TGF‐β are correlated with overall survival in intrahepatic cholangiocarcinoma, while in HCC Ln‐332 cooperates with TGF‐β1, triggering the epithelial‐mesenchymal transition and promoting a more invasive and aggressive phenotype .…”
Section: Discussionsupporting
confidence: 89%
“…Our data supported that HAK-1B exhibited malignant features including higher invasive activity. In addition, Gorvaere et al recently reported that Laminin-332 induced K19 expression via mTORC2 signaling pathway, and Laminin-332 sustained chemoresistance including sorafenib of HCC cell line [26]. However, in our present study, the cytotoxicity of sorafenib or other drugs except for rapalogs was similar for both HAK-1A and HAK-1B cell lines (Table 1).…”
Section: Discussioncontrasting
confidence: 45%
“…Specifically, genetically distinct subclones together with developmental pathways and epigenetic modifications can contribute to functional heterogeneity and chemoresistance 65 . Furthermore, the tumour microenvironment, composed of cancer-associated macrophages, fibroblasts and vascular cells and functioning as a specialized CSC niche, contributes to the maintenance of stemness and chemoresistance [65][66][67] .…”
Section: Cancer Stem Cellsmentioning
confidence: 99%